Human milk oligosaccharides as prebiotics - Gozde Okburan; Serap Kızıler (Elsevier, 2023)
Based on its richness in immune-related components such as human milk, human milk oligosaccharides (HMOs), milk proteins, and lipids, breast milk can be considered the first functional food that humans encounter in their lifetime. According to WHO recommendations breast milk has to be the only food in an infant's diet in the first six months of age which is then continued up to two years of age with the suitable complementary foods. Regarding breast milk balanced composition, it is considered as the best food of infants thus many studies have been carried out to determine the benefits of breast milk. Based on numerous studies breast milk have a tendency to reduce the risk of type 2 diabetes, obesity, allergies, celiac disease, necrotizing enterocolitis (NEC), gastrointestinal tract infections and some type of cancers. The benefits of breast milk can be explained by its special combination which includes; macronutrients, micronutrients and bioactive components such as immunoglobulins, hormones, growth factors and oligosaccharides. One of the essential bioactive compounds of breast milk is known as human milk oligosaccharides (HMOs). HMOs are unique, bioactive carbohydrates which are identified as the most significant components of breast milk. Since they have structural complexity and multifunctional properties, they are one of the most wondered components of breast milk. HMOs promote the development of the neonatal intestinal immune, and nervous systems. This article briefly describes the history, complex structure and different functions of HMOs and highlight the importance of maternal diet for HMO biosynthesis.